(untitled) (Bangladesh Agronomy Journal, 2015)
A two-year experiment was conducted during Rabi season of 2012-13 and 2013-14 at the Regional Wheat Research Centre (RWRC), Bangladesh Agricultural Research Institute, Rajshahi. Recently released six varieties like Shatabdi, Bijoy, Prodip, BARI Gom 25, BARI Gom 26 and BARI Gom 27 were evaluated under raised bed system in randomized complete block design with three replications. The varieties were evaluated for yield, and yield components with some phenological and physiological parameters. The effects of raised bed system over two years were significant for all the parameters. The highest mean yield over tillage method (among the tested varieties) was produced by varieties BARI Gom 27 and Shatabdi followed by BARI Gom 26 and Bijoy varieties. These varieties produced satisfactory yields in raised bed methods. The lowest yielder varieties were Prodip and BARI Gom 25. Considering the overall growth, yield and other characters of three varieties like BARI Gom 27, Shatabdi and Bijoy have been provisionally selected at Rajshahi region as well as in wheat growing areas in Bangladesh. Bangladesh Agron. J. 2014, 17(2): 61-66